Hubungan Kompetensi Perawat dan Pengalaman Kerja dengan Kelengkapan Dokumentasi Transfer Pasien di Rumah Sakit Rizani - Ahmad effendi; Widya Addiarto; Alwin Widhiyanto (An-Najat, 2023)
Nurse competency refers to qualifications of knowledge and skills. and the attitudes needed by a nurse to carry out their professional duties and responsibilities well, knowing the relationship between Nurse competency, work experience and completeness of patient transfer documentation at Rizani Hospital. This research method uses Purposive Sampling with a sample size of 66 respondents. The results of this research show a relationship between nurse competency, work experience, and completeness of patient transfer documentation at Rizani Hospital, which shows a positive and significant relationship between these variables (r = 0.65, p < 0.05).